Pranata-Sosial Pendidikan Islam di Indonesia: Sekolah, Madrasah, dan Pesantren - daman huri; Jamiluddin Yacub (Program Studi Pendidikan Agama Islam, 2024)
Abstract; This research aims to explain philosophically the existence of the three social institutions of Islamic education in Indonesia (schools, madrasas and Islamic boarding schools) and to understand how these three institutions have interacted with the history and cultural diversity of Indonesia. Additionally, the aim of this research is to provide an in-depth understanding of how the educational philosophies at these three institutions have developed and adapted throughout their history. This research uses philosophical and historical analysis methods. Philosophical analysis is used to explore the essence and principles underlying Islamic education in schools, madrasas and Islamic boarding schools. Meanwhile, historical analysis is used to trace the development and historical role of each institution in the context of Islamic education in Indonesia The conclusion is that the rich diversity in Islamic education in Indonesia provides a strong foundation for future development. Through collaboration and cooperation between Islamic education institutions, this potential can be strengthened and utilized to advance Islamic education in Indonesia as a whole and provide valuable insight into the future direction of Islamic education in Indonesia, highlighting the importance of integration between institutions and joint strategies in facing challenges and upcoming opportunities.